Step back : how to bring the art of reflection into your busy life - Badaracco, Joseph, Jr. (Boston, Massachusetts : Harvard Business Review Press, 2020)
"Four simple rules for using reflection to find clarity despite the turbulence of work and life. We all wish we had more time to pause and reflect about small decisions and big goals--and everything in between. But since we live and work in a vortex of tasks, meetings, decisions, and serious responsibilities, we rarely get the chance to step back. In this practical guide, best-selling author and Harvard Business School professor Joseph Badaracco argues that you don't need long periods of solitude and tranquility to reflect well. In fact, reflection can take place in the cracks and crevices of your very busy life, and these moments can help you understand your feelings, look at problems from different perspectives, focus on what really matters, and, ultimately, lead a better life. Building on candid interviews with over a hundred executives and professionals, as well as classic works by Marcus Aurelius, Michel de Montaigne, and Ignatius Loyola, Badaracco offers four rules for reflection that you can customize to the demands of your work and your goals for your life. Concise, smart, and pragmatic, Step Back is the guide you need to make reflection a positive force in your work and life"--
Mosaic reflection -- Aim for good enough -- Downshift occasionally -- Ponder the tough issues -- Pause and measure up.
Includes bibliographical references and index.
Description based on online resource; title from title page (viewed October 1, 2020).
OCLC control number change
Keywords: Critical thinking; Well-being.; Success in business; Critical thinking; Success in business; Well-being.; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; elektronické knihy; electronic books